Comparison of the selenium level with GSH-Px activity in the liver of mice treated with 7,12 DMBA - Batcioglu, K; Ozturk, C; Karagozler, A; Karatas, F (Wiley, 2002)
In this study, the relationship between selenium (Se) and glutathione peroxidase (GSHPx) levels was investigated in 7,12-dimethylbenz(a)anthracene (7,12-DMBA)-treated mouse liver. The potential mammary carcinogen 7,12-DMBA, was injected intraperitoneally (20 mg kg(-1) day(-1)) into 10-12 month old female mice. After 21 days of application the mice were sacrificed and GSHPx and Se levels of Liver homogenates were measured. Se and GSHPx levels in 7,12-DMBA-treated mice were significantly lower than those of controls (p<0.05). The control group exhibited 0.9 +/- 0.066 U mg(-1) protein and 0.86 +/- 0.058 p.p.m. levels of GSHPx and Se respectively. The 7,12-DMBA-treated group had significantly (p<0.05) decreased GSHPx and Se levels (0.42+/-0.062 U mg(-1) protein and 0.69+/-0.034 p.p.m. respectively). The results show a direct relationship between Se and GSHPx activity and a negative correlation between antioxidant capacity and existence of a carcinogen in metabolism. Copyright (C) 2001 John Wiley Sons, Ltd.
Keywords: Se; GSH-Px; 7,12-DMBA